Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s00213-006-0684-9
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of the effects of ethanol on memory, anxiety, and motor behavior in mice tested in the plus-maze discriminative avoidance task

Abstract: Neither the anxiolytic nor the locomotor effects of ETOH seem to be related to its amnestic effect in the PMDAT. Additionally, data give support to the effectiveness of the PMDAT in simultaneously evaluating learning, memory, anxiety-like behavior, and motor activity by different parameters. Possible relationships between the behavioral alterations found are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 60 publications
8
47
2
Order By: Relevance
“…These behaviours can modify retrieval performance, and therefore must be carefully controlled. 17,19,[43][44][45][46] In addition, compared with other aversive memory tests, a difference in motor activity would be a less critical methodological concern in the PM-DAT interpretation because retention is evaluated by the time spent in the aversive versus nonaversive enclosed arms during testing. This was particularly important in the present study because SI increased locomotion in the PM-DAT despite increasing immobility in the FST and in the TST.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These behaviours can modify retrieval performance, and therefore must be carefully controlled. 17,19,[43][44][45][46] In addition, compared with other aversive memory tests, a difference in motor activity would be a less critical methodological concern in the PM-DAT interpretation because retention is evaluated by the time spent in the aversive versus nonaversive enclosed arms during testing. This was particularly important in the present study because SI increased locomotion in the PM-DAT despite increasing immobility in the FST and in the TST.…”
Section: Discussionmentioning
confidence: 99%
“…50 Avoidance of the aversive enclosed arm in the PM-DAT on testing has been validated as a measurement of retention because amnestic manipulations decrease it. 17,19,43,45,46,51 We examined whether the SI-induced depressive-like behaviour would facilitate the retrieval, thereby characterizing an MCM in mice. Thus, the effects of SI were evaluated in an experimental condition in which facilitation of retrieval would not be masked by a ceiling effect produced by an optimal retrieval response in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The storage of the task (and, consequently, the processes of consolidation and recall) is detected by the percent time spent in the aversive enclosed arm in the testing. In this context, the avoidance of the aversive enclosed arm upon testing has been validated as a measurement of retention because amnestic manipulations decrease it (Alvarenga et al, 2008;Claro et al, 1999;Kameda et al, 2007;Patti et al, 2010;Sanday et al, 2012;Frussa-Filho, 2000, 2002;Silva et al, 1999Silva et al, , 2004Zanin et al, in press). In contrast, memory-improving treatments increase such avoidance (Claro et al, 1999;Silva et al, 1997Silva et al, , 1999.…”
Section: Discussionmentioning
confidence: 97%
“…Studies performed previously with the aversive version of the paradigm showed that the total number of entries in all the arms is an adequate indicative of locomotor activity Carvalho et al, 2006;Kameda et al, 2007). In these previous studies, usually a decrease in total number of entries was observed in test session in comparison to training.…”
Section: Discussionmentioning
confidence: 97%